(untitled) (Research, Society and Development, 2024)
This study reports the clinical case of a 28-year-old female patient who sought dental care at the Jardim Farina Basic Health Unit (UBS) in São Bernardo do Campo for the extraction of third molars. During the clinical and radiographic examination, a rare finding was observed: pronounced incisal cingula in the shape of claws on teeth 11, 21, 12, and 22. The panoramic radiograph revealed radiopaque areas associated with these anatomical projections. Although the condition is uncommon, the patient chose not to undergo restorative aesthetic treatment, as she was not bothered by her appearance. This study details the clinical and radiographic characteristics of the condition, reviews relevant literature, and discusses the implications of opting for conservative management.